An Agent Based Green Assessment System Architecture for Sustainable Practice Implementation among IT Practitioners in University Campuses - Bokolo, Anthony Jnr.; Awanis, Romli; Mazlina, Abdul Majid (IEEE, 2017)
Sustainability has progressively become significant to research and practice in educational sector over the year as a result of rapid reduction of natural resources and sudden climatic changes. The fast changing global weather requires Information Technology (IT) practitioners in university institutions to respond to these changes and implement Green strategies and initiatives. However the literature on implementing Green practices by university campuses is still in its infancy, an emphasis on sustainability has been argued to support IT practitioners enhance the use of IT infrastructures, while achieving a sustained university campus. While sustainability has gained increasing attention from researchers and academicians in organizations and industries, sustainability practice implementation in university sector is still not fully successful since IT practitioners currently uses manual based Green assessment methods. IT practitioners in university campuses lack the capability to assess their current Green practices automatically. Therefore there is need for architecture to support IT practitioners in assessing, benchmarking and rating their current Green practice implementation to ascertain if the sustainability goal of economic, people and environment is archived or if they need to improve their Green process implementation. To overcome the aforementioned problems this research proposes an agent based Green assessment architecture to evaluate the current practice implementation in university campuses automatically. The proposed Green assessment system architecture also provides Green process implementation suggestions to IT practitioners.